Pemberdayaan Sumber Daya Manusia Di Bidang Keagamaan Melalui Pelatihan Peningkatan Kompetensi Menggunakan Metode Ummi Bagi Guru TPQ - Fatih, Moh. Khoirul (PARTISIPATORY, 2023)
The results of observations and extracting data that we conducted for the people of Kepodang Hamlet for thirty-four days, showed various phenomena that occurred. Among these phenomena, we took one of the phenomena, namely the less than optimal teaching staff of TPQ Al-Hidayah. The lack of teaching staff resulted in learning at TPQ Al-Hidayah being less than optimal. This problem was used as the focus of research in the 2018 service activities. In an effort to overcome this problem, together with the TPQ management held a training activity entitled "Training for Competency Improvement of Teachers of the Al-Qur'an al-Hidayah Educational Park through the Ummi Method" as a teaching training activity. -Qur'an with the Ummi Method. The training was delivered by Mr. Nur Syamsi, S.Pd. and Mr. Yanto, M.Pd who is a representative of the Ummi Foundation Lamongan with the hope of improving the quality and quantity of teaching staff at TPQ Al-Hidayah. This activity was attended by about 75% of the number of invitations distributed. As a result, the invitees were quite enthusiastic and hoped that there would be an advanced training program that could be implemented as an initial step in improving the teaching competence of TPQ Al-Hidayah teachers.